Problems involved in the conservation of historic buildings in New Zealand: a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy at Massey University - Lewis, Joanne (Massey University, 1984)
This empirical research derives, by way of case studies, the range of problems involved in the conservation of historic buildings in New Zealand. A dichotomy of problems is evident and consequently discussed - legislative/regulatory problems, and problems pertaining to held attitudes. The first category looks at the problems of inadequate legislative provisions for historic building protection (in both the Historic Places Act 1980, and the Town and Country Planning Act 1977), the earthquake standards and design codes, and 'legislative omissions' (a phrase coined to cover aspects neglected in the current legislation). In the second category, conservation problems attributed to the attitudes of government, the public, local authorities, owners/developers, and the Historic Places Trust are discussed as they present a hindrance to the effective protection of historic buildings in New Zealand. Finally recommendations are tendered which, if actioned, would go a long way towards counteracting these problems, and consequently render historic buildings in New Zealand more likely to be conserved.
Keywords: Buildings -- New Zealand; Conservation and restoration